Research and Application of Chondroitin Sulfate/Dermatan Sulfate-Degrading Enzymes - Wang, Wenshuang; Shi, Liran; Qin, Yong; Li, Fuchuan (Frontiers in Cell and Developmental Biology, 2020)
Chondroitin sulfate (CS) and dermatan sulfate (DS) are widely distributed on the cell surface and in the extracellular matrix in the form of proteoglycan, where they participate in various biological processes. The diverse functions of CS/DS can be mainly attributed to their high structural variability. However, their structural complexity creates a big challenge for structural and functional studies of CS/DS. CS/DS-degrading enzymes with different specific activities are irreplaceable tools that could be used to solve this problem. Depending on the site of action, CS/DS-degrading enzymes can be classified as glycosidic bond-cleaving enzymes and sulfatases from animals and microorganisms. As discussed in this review, a few of the identified enzymes, particularly those from bacteria, have wildly applied to the basic studies and applications of CS/DS, such as disaccharide composition analysis, the preparation of bioactive oligosaccharides, oligosaccharide sequencing, and potential medical application, but these do not fulfil all of the needs in terms of the structural complexity of CS/DS.